Maternal and fetal outcome of subsequent pregnancy in patients with documented peripartum cardiomyopathy - Masuku, David Sifiso (Division of Cardiology, 2019)
AIM: Subsequent pregnancies (SSPs) in patients with peripartum cardiomyopathy (PPCM) have a high risk of heart failure relapse. We report on outcome of SSPs in PPCM patients in South Africa. METHODS AND RESULTS: Of the 18 PPCM patients with a SSP, 3 patients died within 6-months follow-up. Overall relapse rate, left ventricular ejection fraction (LVEF) <50% or death after at least 6 months follow-up, was 30%, with 16% (3/18) mortality. Persistently reduced LVEF (<50%) before entering SSP was present in 44% of patients, while full recovery (LVEF≥ 50%) was present in 85%. Persistently reduced LVEF before SSP was associated with a higher mortality (27% vs 0%) and a lower rate of full recovery at follow-up. Patients obtaining standard therapy for heart failure and bromocriptine immediately after delivery displayed significantly better LVEF at follow-up and a higher rate of full recovery, with no patient dying, compared with patients obtaining standard therapy for heart failure alone. CONCLUSION: Full recovery of LVEF before SSP was associated with lower mortality and better cardiac function at follow-up. Addition of bromocriptine to standard therapy for heart failure immediately after delivery was safe and appeared to be associated with better outcome of SSP in our patients.